MODEL PENGELOLAAN PENDIDIKAN MULTIKULTURAL BERBASIS NILAI ISLAM DI SMP IT AL-MUBAROK KABUPATEN TASIKMALAYA - Dede Ropi Fahmi; Rizka Husnu Maulana; Yani Mulyani; Sunan Hanif Ihsan Assalam; Mohamad Erihadiana (Tadbir: Jurnal Manajemen Pendidikan Islam, 2026)
This study is motivated by the urgency of implementing multicultural education in pluralistic societies, particularly within the context of Islamic education. It aims to answer the research question: how is a model of multicultural education management based on Islamic values implemented at SMP IT Al-Mubarok, Tasikmalaya Regency? This research employs a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation. The findings reveal that multicultural education management at SMP IT Al-Mubarok is carried out through three main aspects: (1) planning based on the integration of Islamic and local cultural values; (2) teaching practices that foster tolerance and inclusivity; and (3) continuous evaluation of students' social behavior. This model has a positive impact on strengthening students' character and creating a harmonious school environment amid diversity. The study is relevant as a reference for developing Islamic education management strategies that are responsive to the challenges of multiculturalism in the global era.